2019
DOI: 10.3389/fendo.2019.00885
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal Farnesol and Farnesal in the Mealworm's Alimentary Canal: An Unusual Storage Site Uncovering Hidden Eukaryote Ca2+-Homeostasis-Dependent “Golgicrine” Activities

Abstract: Farnesol, the sesquiterpenoid precursor of the six presently known insect juvenile hormones (JHs) was for the first time chemically identified in 1961, not in JH synthesizing glands or whole body extracts, but in excrements of the mealworm Tenebrio molitor. This finding was thought to be irrelevant and remained unexplored. In 1970, it was reported that the fall to zero of the JH titer in both prediapausing adults and in last instar larvae of the Colorado potato beetle causes severe malfunctioning of the Golgi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 78 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…It is a central meeting point for the endocytotic and exocytotic systems in eukaryotic cells ( Barlow et al, 2018 ). Last but not least, through logical deduction, De Loof and Schoofs (2019b , d) came to the conclusion that the Golgi system is the most probable site of synthesis of endogenousFLSs) (section “The Golgi Apparatus as a Probable Subcellular Site of Synthesis of Farnesol/Farnesol-Like Sesquiterpenoid: Origin of This Idea”).…”
Section: Basic Mechanisms In Ca 2+ Homeostasismentioning
confidence: 99%
See 4 more Smart Citations
“…It is a central meeting point for the endocytotic and exocytotic systems in eukaryotic cells ( Barlow et al, 2018 ). Last but not least, through logical deduction, De Loof and Schoofs (2019b , d) came to the conclusion that the Golgi system is the most probable site of synthesis of endogenousFLSs) (section “The Golgi Apparatus as a Probable Subcellular Site of Synthesis of Farnesol/Farnesol-Like Sesquiterpenoid: Origin of This Idea”).…”
Section: Basic Mechanisms In Ca 2+ Homeostasismentioning
confidence: 99%
“…Ablation of the CA not only affects the Golgi systems but nearly all aspects of cell physiology, including lipid, protein, and ecdysteroid biosynthesis, the multiplication of mitochondria, etc. It visualized in a few images that farnesol esters are indeed the master hormone(s) in insect physiology and development ( De Loof and Schoofs, 2019b , d ). Both reimplantation of active CA and administration of synthetic JH (dissolved in an oil to act as a slow-release formula) temporarily (= within a few days) rescued the observed phenotype and thus demonstrated that absence of farnesol/JH is the real cause of the cell physiological effects induced by allatectomy ( De Loof and Lagasse, 1970 ).…”
Section: The Link Between Ca 2+ Pumping By Sarco(ementioning
confidence: 99%
See 3 more Smart Citations